Biofilm and Enamel Changes after Interproximal Reduction and Polishing - Orozco Molina, Grissel Guadalupe (2026)
This study examined the effects of three different interproximal enamel reduction (IER) techniques and subsequent polishing methods on enamel roughness and biofilm formation. Enamel samples were treated with diamond burs, abrasive strips, or diamond discs, followed by polishing using various techniques. Surface roughness was measured with Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), and Profilometry (PM). Biofilm formation of Streptococcus mutans, Lactobacillus acidophilus, and Candida albicans were evaluated in vitro after IER and polishing. The results shown SEM, AFM, and PM revealed increased roughness on enamel surfaces treated with all IER techniques, with PM showing higher Ra and Rz values for the diamond bur IER method. Polishing was performed after IER, reducing roughness across all methods, though not to control levels. Additionally, a significant increase in the levels of S. mutans, L. acidophilus, and C. albicans was observed on enamel surfaces treated with all IER techniques, with reductions seen after polishing.While IER effectively addresses dental crowding, it inherently increases enamel roughness and consequently elevates the risk of biofilm accumulation and caries. This study emphasizes the importance of meticulous polishing procedures and highlights the need for long-term clinical studies to evaluate the enduring effects of IER on oral health.